A bioinspired adaptive spider web. (17th January 2017) - Zheng, L; Behrooz, M; Gordaninejad, F
Abstract: This work presents an adaptive structure inspired by spider webs' behavior. To investigate the dynamic properties and performance of this system, numerical models are developed to examine the effects of pretension in radial strings, and Young's modulus, and damping ratio on the natural frequency and total energy of the system. An experimental study was conducted to validate theoretical results. Stepper motors controlled by a microcontroller are utilized to increase the pretension in the radial strings of the web in order to tune the web's energy absorption ability. It is demonstrated that the pretension, Young's modulus, and damping ratio in the radial strings can significantly affect the natural frequency and total energy of full and damaged webs. It is also shown that increasing the pretension in the radial strings compensates for the loss of stiffness due to the damaged strings. Finally, it is shown that controlling the pretension in radial strings can provide higher energy absorption capability for the spider web.